2019
DOI: 10.2147/orr.s199107
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparison of gait, functional activities, and patient-reported outcome measures in patients with knee osteoarthritis and healthy adults using 3D motion analysis and activity monitoring: an exploratory case-control analysis</p>

Abstract: ObjectiveTo examine functional performance differences using kinematic and kinetic analysis between participants with and without knee osteoarthritis (OA) to determine which outcomes best characterize persons with and without knee OA.MethodsParticipants with unilateral moderate knee OA (Kellgren–Lawrence grades 2 or 3) and controls without knee pain were matched for age, gender, and body mass index. Primary outcomes included temporal parameters, joint rotations and moments, and ground reaction forces assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Knee joint function, gait speed, and WOMAC scores were lower in the knee OA group than in the healthy group (Table 2). Previous studies have also reported reduced knee extensor strength and gait speed in patients with knee OA compared to those in healthy subjects [68, 24, 25], which means that the results of the present study support those of previous studies. Furthermore, there were significant weak positive correlations between gait cycle variability and 5MWT (r=0.46) and between gait cycle variability and WOMAC (r=0.43).…”
Section: Discussionsupporting
confidence: 91%
“…Knee joint function, gait speed, and WOMAC scores were lower in the knee OA group than in the healthy group (Table 2). Previous studies have also reported reduced knee extensor strength and gait speed in patients with knee OA compared to those in healthy subjects [68, 24, 25], which means that the results of the present study support those of previous studies. Furthermore, there were significant weak positive correlations between gait cycle variability and 5MWT (r=0.46) and between gait cycle variability and WOMAC (r=0.43).…”
Section: Discussionsupporting
confidence: 91%
“…All the subjects who participated in this study had either end-stage osteoarthritis in the hip or knee or had recently recovered from a total joint arthroplasty. This patient population has been shown to exhibit gait adaptations, including a slower pace, shorter step length, reduced knee flexion, and increased levels of variability that may affect the generalization of the model to healthy individuals [ 28 , 48 , 49 , 50 ]. Gait measurements were taken in the laboratory environment, which may affect the subjects’ normal gait patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of gait analysis showed that walking speed and step length of patients with knee osteoarthritis are significantly reduced compared with normal people, and the single support time in the whole gait cycle is significantly longer. The above parameters of patients after TKA will be improved compared with the preoperative parameters, but there is still a certain gap compared with normal gait [33][34][35]. This study mainly compared the effects of GB and MR techniques on postoperative gait in TKA.…”
Section: Discussionmentioning
confidence: 99%